Overview of MPC Applications in Smart Cities - Balbis, Luisella (International Journal of Sensors Wireless Communications and Control, 2021)
Starting from the early 2000s, the concept of Smart City emerged as a new paradigm for urban development, driven by the exponential progress in communication and information technology as well as by the needs of a constant growing population. The Smart City context requires flexible infrastructures and processes, capable of reacting proactively depending on the situation. In this paper, we seek to explore the role of model-based predictive control (MPC) in the development of Smart Cities. The applications of MPC in different scenarios proves that this optimal control strategy is well suited for the dynamic environment in which it operates. Nevertheless, the literature review reveals that real life implementation of MPC as a control strategy within urban setting is still limited and further work is needed to facilitate its adoption in a wider context
Keywords: emergency response